The Bulgarian Catholic Book in the System of the Bulgarian Publishing (1878–1944). Geographic Information Systems as a Tool in Presenting and Preserving Literary Cultural Heritage - Angelova, Gabriela (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2024)
The paper introduces the concept and framework of a scientific project concerning the printed Catholic books in the Bulgarian publishing system between 1878 and 1944. It describes the purpose and the outcomes of implementing Geographic Information Systems within interdisciplinary studies in the Bibliography and Book History scholar fields.
Keywords: Bulgarian Catholic Books; Publishing; Book history; GIS